Riddles of Vedānta and the Revival of Kotta Satchidananda Murty: A Discourse between Liberal & Traditional Standpoints (Journal of the Council for Research on Religion, 2024)
What is the central philosophy of the Upanishads? Is it theistic, monistic, polytheistic, panpsychistic, or something else? Are the world and God real or unreal? Such questions have been a riddle for ancient sages and modern scholars of the Vedāntic tradition, alike. Interestingly, if any thinker has made this discourse more puzzling, it is none other than Śaṅkarācārya (c. 7th–9th centuries CE); through his famous dictum, Brahma satyam jagat-mithya jivo brahmaiva naparah (“Brahman alone is real, the world is unreal. Jiva is not other than Brahman”), he almost changed the entire Vedāntic paradigm, akin to Nietzsche in Western thought with his “God is Dead” dictum. Now, before any thinker embarks on the Vedāntic path, they must first encounter Śaṅkarācārya’s thesis in one way or another, as only then can one engage with notions including ethics, aesthetics, bhakti, karma, and others. Following the same line of inquiry, this review article investigates Professor K. Satchidananda Murty’s distinctive discourse on Vedānta and his engagement with Śaṅkarācārya’s philosophy, as portrayed in a recent edition of some of his works, titled Vedānta and Bhagavadgītā: The Unpublished Writings of K. Satchidananda Murty, proficiently compiled by Professor Ashok Vohra and Kotta Ramesh.